Winged Faith : Rethinking Globalization and Religious Pluralism through the Sathya Sai Movement - Srinivas, Tulasi (Columbia University Press, 2010)
The Sathya Sai global civil religious movement incorporates Hindu and Muslim practices, Buddhist, Christian, and Zoroastrian influences, and ""New Age""--Style rituals and beliefs. Shri Sathya Sai Baba, its charismatic and controversial leader, attracts several million adherents from various national, ethnic, and religious backgrounds. In a dynamic account of the Sathya Sai movement's explosive growth, Winged Faith argues for a rethinking of globalization and the politics of identity in a religiously plural world. This study considers a new kind of cosmopolitanism located